1985
DOI: 10.1677/joe.0.1050201
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and physiological effects of prolactin in incubating ring doves

Abstract: The role of prolactin in the maintenance of incubation behaviour in ring doves was re-examined and the dose-response relationships for behavioural, target tissue and body weight changes induced by injections of prolactin were compared in doves tested during the incubation phase of the breeding cycle. Doves given injections of prolactin twice a day starting on day 4 of incubation, during a 10-day period of isolation from their mates and nests, showed a higher persistence of incubation behaviour than doves injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…Several studies also experimentally demonstrated that the duration of incubation can be extended by artificially increasing prolactin levels of incubating doves (Lea et al, 1986;. Moreover, experimental injection of prolactin restored incubation behavior in doves that were isolated from their nest and egg for several days (Janik and Buntin, 1985), and similarly, experimental injections of prolactin maintain the motivation to incubate in nest-deprived bantam hens (Sharp et al, 1988). All these studies clearly demonstrate the functional role of prolactin secretion in facilitating and maintaining incubation behavior (Silver, 1984;Sharp et al, 1988Sharp et al, , 1998.…”
Section: Prolactin and Parental Behavior In Domestic Birdsmentioning
confidence: 78%
“…Several studies also experimentally demonstrated that the duration of incubation can be extended by artificially increasing prolactin levels of incubating doves (Lea et al, 1986;. Moreover, experimental injection of prolactin restored incubation behavior in doves that were isolated from their nest and egg for several days (Janik and Buntin, 1985), and similarly, experimental injections of prolactin maintain the motivation to incubate in nest-deprived bantam hens (Sharp et al, 1988). All these studies clearly demonstrate the functional role of prolactin secretion in facilitating and maintaining incubation behavior (Silver, 1984;Sharp et al, 1988Sharp et al, , 1998.…”
Section: Prolactin and Parental Behavior In Domestic Birdsmentioning
confidence: 78%
“…Plasma concentrations of prolactin are low in photosensitive birds kept on SD, increase during photostimulation, and are highest at the onset of photorefractoriness (Goldsmith, 1985;Nicholls et al, 1988;Dawson, 1997). This hormone inhibits the reproductive system (Buntin and Tesch, 1985;Janik and Buntin, 1985;Juss, 1993). Thus, elevated circulating prolactin concentrations when birds become photorefractory and shortly thereafter probably contribute to the rapid involution of reproductive tissues that takes place at this time .…”
Section: Discussionmentioning
confidence: 99%
“…Photoinduced high circulating prolactin concentrations are reached during the development of photorefractoriness, when gonads are regressing (Dawson and Goldsmith, 1983;Dawson, 1997;Dawson and Sharp, 1998). Prolactin is not thought to control the transition from photosensitivity to photorefractoriness (Nicholls et al, 1988;Juss, 1993;Dawson and Sharp, 1998), but it participates in the rapid collapse of the reproductive system that characterizes photorefractoriness by inhibiting the hypothalamopituitary-gonadal axis at multiple levels (Buntin and Tesch, 1985;Janik and Buntin, 1985; Sharps et al, 1998).Pituitary prolactin synthesis and release in birds are regulated primarily by vasoactive intestinal polypeptide (VIP; Cloues et al, 1990;Mauro et al, 1992;El Halawani et al, 1995;Youngren et al, 1994). A role for VIP in the reproductive system regression that occurs at the onset of photorefractoriness is suggested by the fact that male European starlings that have been actively immunized against VIP exhibit slower photoinduced regression than control males and do not molt …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is apparent that PRL is involved in many aspects of reproductive physiology and behavior. It plays a pivotal role in parental behavior by mediating increases in incubation, crop milk production and secretion, feeding of young, and nest defense (Silver, 1984;Janik and Buntin, 1985;Buntin et al, 1991).…”
Section: Introductionmentioning
confidence: 99%